2021 Introduction of a new requirement on overheating in residential buildings : Affecting new domestic buildings and other residential buildings including care homes and halls of residence : Final Stage Impact Assessment.: Affecting new domestic buildings and other residential buildings including care homes and halls of residence : Final Stage Impact Assessment. (2021) - Unknown
No abstract available